增強教學之過程：一種知識管理的進路（下） - 何家瑞 (Journal of Education Research (Print), 2014)
Purpose – The purpose of this paper is to emphasize the need for knowledge management (KM) in the teaching-learning process in technical educational institutions (TEIs) India, and to assert the impact of information technology (IT) based KM intervention in teaching-learning process. Design/methodology/approach – The approach of the paper is basically conceptual and descriptive. The paper studies the role of KM in facilitating knowledge sharing among stakeholders in TEIs in India and elaborates on the need for knowledge management in the teaching-learning process. A KM framework for enhancement of knowledge sharing by the use of shared intellectual repositories (IRs) is proposed for the enhancement of teaching and learning in technical educational institutions in India. Findings – The authors value the impact that KM can have in enhancing the quality teaching and learning in TEIs, and underscore the need for credible research into the benefits and challenges that the implementation of IT-based KM intervention